Energy availability in athletics: Health, performance, and physique - Melin, A. K.; Heikura, I. A.; Tenforde, A.; Mountjoy, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Track and field athletes have intense physiological demands and require optimized nutrition (Burke et al., 2019; Slater et al., 2018; Stellingwerff et al., 2018; Sygo et al., 2019). Track and field athletes may experience low energy availability (LEA) due to disordered eating (DE) behavior, inadvertently due to lack of appetite or poor nutritional knowledge, or intentionally to achieve a discipline-specific physique to optimize performance (Burke et al., 2018c; Melin et al., 2015; Mooses & Hackney, 2017; Sygo et al., 2018). LEA may result in adverse health outcomes, increased risk of musculoskeletal injuries, and impaired athletic performance (Figure 1; De Souza et al., 2014; Mountjoy et al., 2018; Nattiv et al., 2007). The purpose of this review is to describe LEA and potential physiological and psychological consequences in the context of athletics and to provide recommendations regarding prevention, early detection, and treatment to achieve safe participation in sport for optimal health and performance.